How girls achieve - Nuamah, Sally A., 1989- (Harvard University Press, 2019)
"This bold and necessary book points out a simple and overlooked truth: most schools never had girls in mind to begin with. That is why the world needs what Sally Nuamah calls feminist schools, deliberately designed to provide girls with achievement-oriented identities. And she shows why doing so would help all students, regardless of their gender."--Provided by publisher